Diverse Bacterial Communities From Qaidam Basin of the Qinghai–Tibet Plateau: Insights Into Variations in Bacterial Diversity Across Different Regions - Zhang, Wei; Bahadur, Ali; Zhang, Gaosen; Zhang, Binglin; Wu, Xiukun; Chen, Tuo; Liu, Guangxiu (Frontiers in Microbiology, 2020)
The Qaidam Basin of the Qinghai-Tibet Plateau is a cold hyper-arid desert that presents extreme challenges to microbial communities. As little is known about variations between surface and subsurface microbial communities, high-throughput DNA sequencing was used in this study to profile bacterial communities of the soil samples collected at different depths in three regions in the Qaidam Basin. The α-diversity indices (Chao, Shannon, and Simpson) indicated that the bacterial abundance and diversities were higher in the East and High-elevation regions compared to the West region. In general, Firmicutes was dominant in the West region, while Proteobacteria and Acidobacteria were dominant in the East and High-elevation regions. The structure of the bacterial communities differed greatly across regions, being strongly correlated with total organic carbon (TOC) and total nitrogen (TN) content. The differences in bacterial communities between the surface and subsurface soil samples were smaller than the differences across the regions. Network analyses of environmental factors and bacterial genera indicated significant positive correlations in all regions. Overall, our study provides evidence that TOC and TN are the best predictors of both surface and subsurface bacterial communities across the Qaidam Basin. This study concludes that the bacterial community structure is influenced by both the spatial distance and local environment, but environmental factors are the primary drivers of bacterial spatial patterns in the Qaidam Basin.